EVALUATION OF MARRIAGE MANAGEMENT INFORMATION SYSTEM (SIMKAH) POLICY IN THE OFFICE OF RELIGIOUS AFFAIRS (KUA) SUB-DISTRICT MARISA, POHUWATO REGENCY - Sri Yulianty Mozin; Yacob Noho Nani; Saiful Annam (International Interdisciplinary Conference on Sustainable Development Goals, 2022)
The aims of this study is to evaluate the Marriage Management Information System (SIMKAH) policy at the Office of Religious Affairs (KUA) Marisa District, Pohuwato Regency seen from the aspects of effectiveness, adequacy, responsiveness, and accuracy, as well as to identify and analyze the factors that influence Information System policies. M. The process of checking the validity of the data is done through triangulation and extension of observations.The results of this study that (1) SIMKAH policy in KUA Marisa District, Pohuwato Regency from the aspect of effectiveness has not achieved the desired results. From the aspect of adequacy, it can solve problems in marriage registration services. From the aspect of responsiveness, the target group of SIMKAH users has not been satisfied. From the aspect of accuracy, it has not provided significant benefits to the community; (2) The factors that become obstacles in the SIMKAH policy process at KUA are (a) the contents of the SIMKAH policy are not yet detailed about the policy objectives, (b) the support and commitment of the Marisa District Government and the Pohuwato Regency Government to the SIMKAH program are still lacking, (c) ) policy resources have not been adequate, both from human resources for operators, budget for information system maintenance and information system infrastructure.